RECURRENCE OF BREAST CANCER AFTER SUBCUTANEOUS MASTECTOMY WITH SIMULTANEOUS RECONSTRUCTION - A. D. Zikiryakhodzhaev; E. A. Rasskazova (Исследования и практика в медицине)
Objective. To analyze the recurrence after radical subcutaneous mastectomy or konohana of mastectomy.Materials and methods. In FMIC them.P. A. Herzen patients performed radical subcutaneous mastectomy (95,5%) or konohana radical mastectomy (4.5 per cent). When radical subcutaneous mastectomy keep the skin of the breast, the nipple-areola complex (NAC), submammary fold, remove the entire gland tissue together with the axillary, subclavian and subscapularis lymph nodes. Konohana mastectomy differs from subcutaneous mastectomy with removal of the nipple-areola complex. Distribution of patients according to tumor stage process as follows: 0 (ТisN0М0) - 33 (4,3%), I - 180 (23,2%), IIA - 283 (36,6%), IIB - 123 (15,9%), IIIA - 91 (11,7%), IIIБ - 1 (0,1%), IIIС - 41 (5,3 %) IY - 6 (0,8%), 16 (2,1%) patients the operation was performed after recurrence of breast cancer.Results. In our study the recurrence was diagnosed in 37 (4,8%) patients. A minimum of recurrences of 8 months, maximum 10 years. Repeated local recurrences after treatment was 2. Local recurrence was diagnosed in 35 (4,5%) patients. Regional recurrence was diagnosed in 3 (0,4%) of patients, in one case after local recurrence. Regional recurrences detected in 2 (0,3%) cases in the armpit and 1 (0,1%) case in the infraclavicular region. The likelihood of regional recurrence is often associated with errors in surgical technique the operation. During follow-up revealed 3 (0,4%) cases of cancer Paget’s disease in the area of the nipple-areola complex. All 3 (0,4%) of cases the treatment was surgical and meant excision of the nipple-areola complex. In 1 (0,1%) patients diagnosed with breast cancer in the second breast after 7 years.In the area of the nipple-areola complex in the Central quadrant of the recurrence was diagnosed in 6 of the 35 local recurrence, which amounted to 17,1%. Among patients with konohana radical mastectomy recurrence in the Central quadrant is not revealed. The distribution of recurrence depending on the stage of breast cancer: in stage I of 5,5%, IIA - 3,5%, IIB - 5,7%, IIIA – 4,4% in S of 7,3%. In 2 cases after the first relapse of 16 was diagnosed with a relapse, which was 12.5%. In stage I breast cancer  as diagnosed with a relapse of 5,5%, which is probably due to the absence of radiation therapy in the postoperative period, since the initial stage and the operation volume is sufficient, the number of relapse - 10 and in any case, radiation therapy was not carried out.Conclusion. Over the 5 years of observation for patients with breast cancer after radical subcutaneous mastectomy/ konohana radical mastectomy with simultaneous reconstruction, recurrence developed in 34 cases (4.4%) patients. The important fact is the detection of local recurrence after 10 years of follow-up (8,1%) after treatment, which confirms the need for dynamic monitoring of patients throughout life. The frequency of relapses affected by stage of breast cancer, young age of patients, the histogenesis and subtype of the tumor. When combined adverse prognostic factors should be used for reoperation on the breast. Radical subcutaneous mastectomy or konohana radical mastectomy with simultaneous reconstruction of an adequate volume of transactions in the cancer plan, and effective method of reabilitacii breast cancer patients. Relapse of breast cancer after these surgeries is not different from the risk of recurrence after radical mastectomy. Despite the presence of repeated operations, the preservation of the reconstructed breast cancer after recurrence of breast cancer was possible in 65, 7% of cases in our study.